A Comparative Study of Static and Dynamic Characteristics of Parabolic and Plane Inclined Slider Bearings Lubricated with MHD Couple Stress Fluids. Issue 1 (2nd January 2017) - Naduvinamani, N. B.; Siddangouda, A.; Siddharam, P.
ABSTRACT: In this article the couple stress effects on the static and dynamic characteristics of parabolic and plane inclined slider bearings in the presence of an applied magnetic field with squeeze action is analyzed theoretically. The modified magnetohydrodynamic (MHD) couple stress Reynolds equation is derived. The closed-form solution for the film pressure of parabolic and inclined plane slider bearings is obtained and used to study the MHD couple stress static and dynamic characteristics of these bearings. The results predict a higher steady load-carrying capacity, dynamic stiffness, and damping coefficient for the bearings lubricated with MHD couple stress fluid than the corresponding Newtonian case. It is observed that the parabolic-shaped slider bearings provide greater steady load-carrying capacity, dynamic stiffness, and damping coefficients compared to the plane inclined slider bearings.